A novel approach to utilizing the essential public health functions in Ireland's health system recovery and reform - McNicholas, Triona; Hendrick, Louise; McDarby, Geraldine; Mustafa, Saqif; Zhang, Yu; Saikat, Sohel; Jakab, Zsuzsanna; Holohan, Tony (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict.’ The COVID-19 pandemic presented a challenge to health systems and exposed weaknesses in public health capacities globally. As Ireland looks to recovery, strengthening public health capacities to support health systems resilience has been identified as a priority. The Essential Public Health Functions (EPHFs) provide an integrated approach to health systems strengthening with allied sectors and their operationalization supports health systems and multi-sectoral engagement to meet population needs and anticipate evolving demands. The Health Systems Resilience team (World Health Organization, HQ) in collaboration with the Department of Health (Ireland) developed a novel approach to the assessment of the EPHFs in Ireland. The approach involved a strategic and focused review of the delivery and consideration of EPHFs in relation to policy and planning, infrastructure, service delivery, coordination and integration, monitoring and evaluation and learning. Informed by a literature review and key document search, key stakeholder mapping and key informant interviews, lessons learned from experience with COVID-19 nationally and internationally, strengths as well as potential areas of improvement to optimize delivery of EPHFs were identified. Mapping of the EPHFs in Ireland revealed that there is evidence of delivery of all 12 EPHFs to varying degrees; however a number of challenges were identified, as well as numerous strengths and opportunities. Recommendations to optimize the delivery of EPHFs in Ireland include to integrate and coordinate EPHFs, increase the visibility of the public health agenda, leverage existing mechanisms, recognize and develop the workforce, and address issues with the Health Information System. There is a public health reform process currently underway in Ireland, with some of these recommendations already being addressed. The findings of this process can help further inform and support the reform process. Given the current focus on strengthening public health capacities globally, the findings in Ireland have applicability and relevance in other WHO regions and member states for health systems recovery and building back better, fairer and more resilient health systems.